Some testicular characteristics of Şavak Akkaraman rams and their relationship with live weight - YAĞCI, S; BAŞ, S (Journal of the Hellenic Veterinary Medical Society, 2022)
In this study, relationships between body weight and testicular characteristics were investigated in Şavak Akkaraman rams. Measurements taken from 60 rams in 7 traditional breeding farms were subjected to variance analysis to determine effects of the ram’s age and the farm, and correlations between traits were calculated. Live weight (LW) average in rams was determined as 74.74±1.33 kg. Scrotum circumference (SC), scrotum width (SW), scrotum length (SL), scrotum thickness (ST), scrotum-ground distance (SGD), right testicular length (RTL), left testicular length (LTL), right testicular diameter (RTD) and left testicular diameter (LTD) values were calculated as 32.98±0.28 cm, 11.27±0.11 cm, 19.11±0.28 cm, 0.597±0.20 cm, 26.30±0.41 cm, 14.31±0.14 cm, 13.91±0.14 cm, 7.15±0.07 cm, 6.78±0.07 cm, respectively. Positive and significant correlations were determined between the body weight of the rams and testicular characteristics, except for SGD measurement. Correlation coefficients between LW and SD (0.620), RTL and LTL (0.541 and 0.524), RTD and LTD (0.676 and 0.561) were high. This study is the first study to determine the relationship between body weight and testicular characteristics in Şavak Akkaraman rams. Due to the limited number of studies on Şavak Akkaraman rams; considering the correlation findings between testicular measurements and live weight, it can be said that morphometric testis measurement results can contribute to future studies as a preliminary information and a descriptive study.